1992
DOI: 10.1177/036354659202000504
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament reconstruction using a composite collagenous prosthesis

Abstract: We evaluated a prototype composite collagenous anterior cruciate ligament replacement device designed to possess the advantages of biological grafts and synthetic materials. Collagenous anterior cruciate ligament prostheses were made by embedding 225 reconstituted type I collagen fibers in a type I collagen matrix, and placing polymethylmethacrylate bone fixation plugs on the ends. The collagenous prosthesis was used to replace the anterior cruciate ligament of 31 mature rabbits. At 4 and 20 weeks postimplanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(74 citation statements)
references
References 29 publications
1
71
1
1
Order By: Relevance
“…In the early 1990s Dunn et al [63] reported initial work on the development of a ligament prosthesis involving a collagenous ACL prosthesis [63]. Results showed inconsistent neoligament formation and significant weakening of the prosthesis in a rabbit model.…”
Section: Scaffolds For Tissue Engineeringmentioning
confidence: 99%
“…In the early 1990s Dunn et al [63] reported initial work on the development of a ligament prosthesis involving a collagenous ACL prosthesis [63]. Results showed inconsistent neoligament formation and significant weakening of the prosthesis in a rabbit model.…”
Section: Scaffolds For Tissue Engineeringmentioning
confidence: 99%
“…Few attempts at creating a bioengineered ACL (bACL) have been reported (Dunn et al 1992(Dunn et al , 1993(Dunn et al , 1994. A drawback of Dunn's approach (Dunn et al 1994) is that the matrix of the graft cannot be quickly degraded, and its remodelling is impaired.…”
Section: Introductionmentioning
confidence: 99%
“…These stages are hydration, depolymerization, loss of mass integrity, absorption, and elimination. This polymer was chosen because of its mechanical retention and its in vitro cellular response to primary rabbit ACL cells (6,(11)(12)(13)(14).Rabbits are one of the most commonly used animals for orthopedic surgery in vivo studies (1,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Adult New Zealand White rabbits were used in this study because rabbits are relatively high-level vertebrates, having a size that enables surgical operations, convenient histology, and mechanical analysis.…”
mentioning
confidence: 99%
“…Several groups have explored ligament-like scaffolds with collagen fibers, silk, biodegradable polymers and composites with limited success (1)(2)(3)(4)(5)(6). During this study, we fabricated an absorbable polyL-lactide (PLLA) 3D, braided TEL replacement capable of supporting the growth and phenotypic expression of cells when seeded in vitro.…”
mentioning
confidence: 99%
See 1 more Smart Citation